Thoracic branched endograft for traumatic aortic pseudoaneurysm - Joseph M. Besho, MD, ScM; Akiko Tanaka, MD, PhD; Zain Al-Rstum, MD; Hunter M. Ray, MD; Bruce Tjaden, MD; Naveed U. Saqib, MD, FACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
Thoracic endovascular aortic repair is the standard treatment for blunt traumatic aortic injuries (BTAI). Approximately 40% of patients with BTAI require left subclavian artery (LSA) coverage for adequate proximal seal. Intentional LSA coverage is not benign; it is associated with complications including stroke, spinal cord ischemia, vertebrobasilar, and left arm ischemia. To avoid these devastating complications, LSA revascularization is recommended before elective zone II thoracic endovascular aortic repair, but is often omitted during emergent cases. We report two cases of aortic zone II traumatic grade III BTAI (aortic pseudoaneurysm) that we successfully treated with the GORE prior to TAG thoracic branch endoprosthesis. Keywords: Thoracic branched endograft, Grade III aortic injury, Zone II, Pseudoaneurysm